Sorghum aphid/greenbug: current research and control strategies to accelerate the breeding of aphid-resistant sorghum - Jiao, Zhiyin; Wang, Jinping; Ma, Xue; Shi, Yannan; Wang, Zhifang; Guo, Yongchao; Lv, Peng (Frontiers in Plant Science, 2025)
Sorghum, one of the world’s five major cereal crops, faces significant yield losses due to aphid infestations, particularly from the sorghum aphid (Melanaphis sacchari) and the greenbug (Schizaphis graminum). These pests not only cause a reduction in grain yield, but also transmit plant viruses, posing a serious threat to global food security. Current strategies to mitigate aphid damage include large-scale insecticide applications, biological control through natural enemies, and the development of aphid-resistant sorghum varieties. However, the resistance genes of aphids and their mechanisms are still unclear, which poses a major challenge to breeding programs. This review synthesizes recent advances in understanding the interactions between sorghum and these two major aphid species, exploring topics such as aphid classification, quantitative trait locus (QTL) mapping of resistance genes, and the molecular mechanisms of sorghum-aphid interactions. We also discuss conventional and emerging insecticide methods, biological control strategies, and their associated challenges. Looking ahead, the integration of molecular breeding techniques, including genetic engineering and genome editing, holds promise for accelerating the development of aphid-resistant sorghum varieties. These innovative approaches aim to minimize aphid damage, enhance sorghum productivity, and contribute to global food security in the face of climate change and evolving pest pressures.